Numerical Modelling of the Effect of a Magnetic Field on Dynamic Configuration During the Solidification Process of a Metallic Alloy - ABDELHAKEM, Abdelhafidh; HACHAN, Lakhdar (Université de Laghouat , Bibliothèque centrale, 2022)
This work aims to contribute to the development of a numerical model that predicts the effect of natural and forced convection on the phase change of metallic alloys. The geometrical configuration considered throughout this study was chosen to correspond to the crucible of an experimental benchmark called 'AFRODITE', developed at the SIMAP-EPM laboratory in Grenoble/France. A 3D numerical model was proposed based on the enthalpy approach (to treat cases of solidification of metal alloys with the segregation phenomenon) under the influence of natural convection and forced convection caused by electromagnetic stirring. This model has been applied in order to better understand, master and control the solidification process of metallic alloys, in terms of defects that occur during the solidification, particularly segregation at the meso and macroscopic scale. The developed numerical model was validated by in-situ and real-time measurements of temperatures at any point of the solidification system, which allows quantitative and qualitative validation.